2019
DOI: 10.7150/ijbs.31972
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of DNA Damage Factor RNF8 in the Pathogenesis and Progression of Cancer

Abstract: The really interesting new gene (RING) finger protein 8 (RNF8) is a central factor in DNA double strand break (DSB) signal transduction. DSB damage is the most toxic type of DNA damage to cells and is related to genomic instability. Multiple roles for RNF8 have been identified in DNA damage response as well as in other functions, such as telomere protection, cell cycle control and transcriptional regulation. These functions are closely correlated to tumorigenesis and cancer progression. Indeed, deficiency of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…Additionally, increased expression of Pttg1 causes errors in chromosome segregation during mitosis due to increased genomic instability [ 76 ]. RNF8 functions in the signaling of DSBs through the mono-ubiquitination of H2A and H2B [ 77 , 78 ]. RNF8 deficiency has been associated with tumor development, probably due to increased genomic instability [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of Pttg1 causes errors in chromosome segregation during mitosis due to increased genomic instability [ 76 ]. RNF8 functions in the signaling of DSBs through the mono-ubiquitination of H2A and H2B [ 77 , 78 ]. RNF8 deficiency has been associated with tumor development, probably due to increased genomic instability [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin E3 ligase RNF8, which primarily functions in transducing DSB signals by conjugating ubiquitin to histones [22], has been reported to participate in tumorigenesis because RNF8 knockout mice develop various tumors spontaneously [44][45], indicating a negative role of RNF8 in tumorigenesis. However, RNF8 appears to have the opposite effect in tumor progression according to recent studies, because it promoted breast cancer proliferation and metastasis by affecting the Wnt/β-catenin pathway and activating the activity of transcription factors such as Twist and ERα [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…RING finger protein 8 (RNF8), which belongs to the RING finger E3 ligase family, is an essential factor for transducing DNA double-strand breaks (DSB) signaling [20][21][22]. It has been reported to be highly expressed in breast cancer and positively correlated with the progression of breast cancer by activating the Wnt/β-catenin pathway or enhancing the activity of Twist and estrogen receptor α (ERα) [23][24][25].…”
Section: Ivyspringmentioning
confidence: 99%
“…The role of RNF8 in tumor development and progression exhibits a double-sided action, resulting in either tumor inhibition or promotion. In a mouse model, the downregulation or loss of RNF8 results in a significant increase of tumor incidence, including the incidence of leukemia in tumorigenesis of lymphoma (50%), thymoma (38%), mammary carcinoma (13%), skin tumor (13%) and sarcoma (13%) ( 30 ). A previous study has revealed that the expression levels of P53 are significantly increased in RNF8-knockout mice ( 12 ).…”
Section: Discussionmentioning
confidence: 99%